Analisis Rencana Pembelajaran Berdasarkan Penilaian Berbasis Kelas - Naryatmojo, Deby Luriawati; Wati, Maulida Laily Kusuma; Subyantoro (GERAM: Gerakan Aktif Menulis, 2022)
This study aimed to understand how to implement class-based assessment in the lesson plan that covered class-based cognitive aspects, class-based affective aspects, and class-based psychomotor aspects. This study used research subjects, including lesson plans and essay review materials on Indonesian topics, level 2 high school lesson plans, fiction text materials, and level 3 high school lesson plans with historical text materials. The research employed a qualitative descriptive approach. The source of data was three lesson plans with different texts and topics. The reserach findings reveal that the first lesson plan does not include a self-assessment sheet that can be used as an instrument in assessing students' effectiveness. In contrast, the second and third lesson plans have fulfilled all assessment forms related to students' cognitive, affective, and psychomotor assessments.